2022
DOI: 10.1101/2022.09.14.507935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for breadth development in a HIV-1 neutralizing antibody

Abstract: Antibody affinity maturation enables adaptive immune responses to a wide range of pathogens. In some individuals broadly neutralizing antibodies develop to recognize rapidly mutating pathogens with extensive sequence diversity. Vaccine design for pathogens such as HIV-1 and influenza have therefore focused on recapitulating the natural affinity maturation process. Here, we determined structures of antibodies in complex with HIV-1 Envelope for all observed members and ancestral states of a broadly neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the case of our apex-stapled design, a differing folded state population was readily identified in our cryo-EM three-dimensional (3D) classification. No such state has been identified in any of our related SOSIP constructs (39,58,71,72), nor were substantial lotto-lot quality control variations observed that would indicate fold instability. Furthermore, a different fold would likely result in a distinct thermal denaturation profile, so a discernible bi-or multimodal denaturation profile would be expected.…”
Section: Discussionmentioning
confidence: 90%
“…In the case of our apex-stapled design, a differing folded state population was readily identified in our cryo-EM three-dimensional (3D) classification. No such state has been identified in any of our related SOSIP constructs (39,58,71,72), nor were substantial lotto-lot quality control variations observed that would indicate fold instability. Furthermore, a different fold would likely result in a distinct thermal denaturation profile, so a discernible bi-or multimodal denaturation profile would be expected.…”
Section: Discussionmentioning
confidence: 90%
“…In the case of our apex stapled design, a differing folded state population was readily identified in our cryo-EM 3D classification. No such state has been identified in any of our related SOSIP constructs (42,49,90,133), nor were substantial lot-to-lot quality control variations observed that would indicate fold instability. Further, a different fold would likely result in a distinct thermal denaturation profile, so a discernable bi or multimodal denaturation profile would be expected.…”
Section: Discussionmentioning
confidence: 91%
“…Also key is the use of immunogens that can select for bnAb B cell maturation events that allow lineage members to bind and/or accommodate Env glycans. Accommodation of the V1 loop is a critical milestone in the generation of V3-glycan-targeted bnAbs ( 5 , 6 , 33 , 34 , 52 ). Here we used an Env with V1 glycans deleted as a prime ( 6 ) and an Env with the V1 glycans restored as a boost to select for V3-glycan bnAb lineage improbable mutations.…”
Section: Discussionmentioning
confidence: 99%